PENGARUH CORPORATE GOVERNANCE TERHADAP INNTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN MAUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Adinda Maihartati; Makhdalena Makhdalena; Riadi Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the influence of corporate governance that represented by audit comitte, independent commissioner and managerial ownership on integrity of financial statement both of simultaneously and partially at manufacturing companies which is listing in the Indonesia Stock Exchange for 2015 until 2017. The population of this study is all of the manufacturing companies which is listing in the Indonesia Stock Exchange for 2015 until 2017 which has complete data about audit comitte, independent commisioner, and managerial ownership and examined by census. This study used secondary data sourced from annual report. The data analysis technique used multiple linier regression with the help of the program called SPSS (Statistical Package for Social Science). The result of this study showed that corporate governance that represented by audit comitte, independent commissioner and managerial ownership simultaneously had an influence on integrity of financial statement. Audit comitte partially had a negative influence on integrity of financial statement. Independent commissioner had a positive inluence on integrity of financial statement. While managerial ownership had a positive influence on integrity of financial statement.Key Words: Corporate Governance and Integrity of Financial Statement